Systematic Review: Study of the Prescribing Pattern of Antibiotics in Outpatients and Emergency Departments in the Gulf Region - Mahmood, Rana Kamran; Gillani, Syed Wasif; Saeed, Muhammad Waqas; Hafeez, Muhammad Umar; Gulam, Shabaz Muhammad (Frontiers in Pharmacology, 2020)
To study the prescribing pattern of antibiotics in the outpatient and emergency department of the Gulf region. To compare the appropriateness of prescriptions and antibiotics commonly prescribed for the respiratory tract infection. Search was limited from 2008 to 2020 and articles must be in English. Articles searched from various resources and are evaluated using PRISMA. 41 articles selected and screened at the end 17 articles included in the study. All articles selected from the gulf region of 7 countries that are UAE, Saudi Arabia, Qatar, Oman, Yemen and Kuwait. Only primary literatures are included. Inpatient and literatures from other countries except gulf region are excluded. Penicillins, cephalosporins and macrolides are highly used antibiotics for respiratory tract infection. Ceftriaxone IV is recommended in acute respiratory tract infection, if therapy failed with penicillin. Most of the prescriptions in Gulf countries for antibiotics are inappropriate. Inappropriate antibiotics prescribing in the gulf region varies from place to place and reaches maximum up to 80%. Antibiotics may be prescribed with the wrong dose, frequency and inappropriate guidelines. Penicillins are prescribed about 50 to 60% most common penicillin prescribed are amoxicillin and co-amoxiclave, cephalosporins are prescribed about 30% most common are third generation, macrolides are prescribed about 17 to 20% most common macrolides are azithromycin and clarithromycin, and fluoroquinolones are prescribed about 10-12% of which levofloxacin and ciprofloxacin are more commonly prescribed and metronidazole as 10%. It is suggested that antibiotics prescribing pattern in out-patient and emergency departments in Gulf region are highly inappropriate, most prescribed antibiotic is amoxicillin/co-amoxiclave and mostly encountered infection in outpatient are acute respiratory tract infection.